2005
DOI: 10.1194/jlr.m500129-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-lowering effects of dietary blue lupin (Lupinus angustifolius L.) in intact and ileorectal anastomosed pigs

Abstract: The present study was undertaken to investigate the effect of cholesterol-enriched casein (CAS) and blue lupin seed (BL) diets on the cholesterol metabolism of intact (INT) and ileorectal anastomosed (IRA) pigs. For 3 weeks, four groups of six pigs were allocated to the treatments (CAS-INT, CAS-IRA, BL-INT, and BL-IRA). Diet-induced hypercholesterolemia was inhibited by the BL through a substantial decrease in plasma LDL-cholesterol. The BL also reduced liver esterified and total cholesterol, increased hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 50 publications
4
55
0
3
Order By: Relevance
“…Another model applied to narrow-leaf lupin was the hyperlipidaemic pig, initially in 2005 (Martins, Riottot, de Abreu, Viegas-Crespo, Lança, Almeida, et al, 2005) and then again in 2014 (Radtke, Geissler, Schutkowski, Brandsch, Kluge, Duranti, et al, 2014). In both researches, significant decreases of total and LDL-cholesterol were observed: in the former the changes in total cholesterol and LDL-C were -29.2% and -37.9%, respectively, in the latter the changes were -32.6% and -28.9%, respectively.…”
Section: Animal Studiesmentioning
confidence: 96%
“…Another model applied to narrow-leaf lupin was the hyperlipidaemic pig, initially in 2005 (Martins, Riottot, de Abreu, Viegas-Crespo, Lança, Almeida, et al, 2005) and then again in 2014 (Radtke, Geissler, Schutkowski, Brandsch, Kluge, Duranti, et al, 2014). In both researches, significant decreases of total and LDL-cholesterol were observed: in the former the changes in total cholesterol and LDL-C were -29.2% and -37.9%, respectively, in the latter the changes were -32.6% and -28.9%, respectively.…”
Section: Animal Studiesmentioning
confidence: 96%
“…20,21 In addition, results obtained from several animal studies suggest cholesterol-lowering effects of lupin. Cholesterol lowering has been observed in chickens 22 and pigs 23 fed whole lupin grain. Other data suggest that protein and fibre isolates from lupin may improve serum lipids.…”
Section: Introductionmentioning
confidence: 95%
“…[14][15][16]22 Limited data from human and animal studies suggest that a lupin-enriched diet may benefit serum lipids and lipoprotein. 24,49 However, we previously showed that an ad libitum lupin flour-enriched diet over 4 months also had no benefit on the serum lipid profile. 11 The lack of effect on blood lipids in our studies may be because of a number of factors.…”
Section: At 4 Monthsmentioning
confidence: 99%
“…20,21 In a previous 16-week trial, we showed that consumption of lupin flour-enriched bread reduced 24-h systolic blood pressure by 3.0 mm Hg. 22 Lupin-enriched diets have also been shown to reduce blood cholesterol concentrations in animals [23][24][25] and humans. 26 Furthermore, acute reductions in postprandial glucose and insulin have been demonstrated with lupin flour-enriched bread consumption, 12,27 but longer-term effects are not clear.…”
Section: Introductionmentioning
confidence: 99%